Immediate effect of valgus bracing on knee joint moments in meniscectomised patients: An exploratory study. Issue 12 (December 2016) - Thorning, Maria; Thorlund, Jonas B.; Roos, Ewa M.; Wrigley, Tim V.; Hall, Michelle
Abstract: Objectives: Patients undergoing medial arthroscopic partial meniscectomy are at increased risk of developing and/or progressing knee osteoarthritis, with increased medial compartment load being a potential contributor. The aim of this study was to evaluate the immediate effect of a valgus unloader knee brace on knee joint moments in patients following medial arthroscopic partial meniscectomy. Design: Within-participant design. Methods: Twenty-two patients (age 35–55 years) who had undergone medial arthroscopic partial meniscectomy within the previous 8–15 months completed three-dimensional analysis of gait, forward lunge and one-leg rise during two conditions: with and without a valgus unloader knee brace. Outcome measures included the peak and impulse of the knee adduction moment and the peak knee flexion moment. Results: The peak knee flexion moment increased during brace condition for forward lunge (mean difference [95% CI]) 0.54 [0.27–0.82] (Nm/(BW × HT)%), p  < 0.001 and one-leg rise (mean difference 0.45 [95% CI 0.08–0.82] (Nm/(BW × HT)%), p  = 0.022). No other significant differences were found between conditions in any of the included tasks. Conclusions: A significant effect of the knee brace was detected in terms of an increase in peak knee flexion moment during the more demanding tasks such as forward lunge and one-leg rise. This increase implies enhanced stability of the knee provided by the brace, which may induce increased knee function and knee-related confidence during strenuous tasks. Future research is required to explore the structural implications.